2020
DOI: 10.3389/fphar.2020.00294
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mapping of Angelica sinensis (Oliv.) Diels (Danggui) Research: A Scientometric Study

Abstract: Background: Traditional Chinese medicine (TCM) has been widely accepted and applied worldwide, and many publications related to Angelica sinensis (Oliv.) Diels (AS, Chinese name is "Danggui") have been published. However, to date, there has not been a scientometric study to systematically analyze the intellectual landscape and emerging research trends regarding AS. Therefore, we performed a scientometric study to address this gap. Methods: Publications related to AS published from 2009 to 2018 were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 51 publications
(96 reference statements)
0
44
0
Order By: Relevance
“…Co-cited references are references that have been cited together by other publications. However, the knowledge base is the collection of co-cited references cited by the corresponding research community (41,(53)(54)(55), which is not entirely equivalent to highly cited references. In this bibliometric analysis, the top 10 references co-cited by the included ferroptosis literature (Table 6) were as follows.…”
Section: Knowledge Basementioning
confidence: 99%
“…Co-cited references are references that have been cited together by other publications. However, the knowledge base is the collection of co-cited references cited by the corresponding research community (41,(53)(54)(55), which is not entirely equivalent to highly cited references. In this bibliometric analysis, the top 10 references co-cited by the included ferroptosis literature (Table 6) were as follows.…”
Section: Knowledge Basementioning
confidence: 99%
“…Firstly, we used the scientometric method to systematically analyze the DILI-related publications for the first time, which could comprehensively guide the clinicians and scholars focusing on DILI. Secondly, we used four scientometric tools to performed this investigation simultaneously, and three of them (HistCite, VOSviewer, and CiteSpace) have been widely used in the scientometric field (Gao et al, 2019;Huang et al, 2019;Lu et al, 2020). Thus, the data analysis process may be objective.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The scientometric analysis also identifies development trends and research hotspots in many fields (Garas et al, 2020;Miao et al, 2018;Gao et al, 2019;Lu et al, 2019a). Using this method, Lu et al (Lu et al, 2020) reported that currently the researches on Angelica sinensis (AS) were focused on identifying and assessing its active components (like ferulic acid) and pharmacological actions (such as immunomodulatory effects). Miao et al (Miao et al, 2018) analyzed the researches on hepatocellular carcinoma, especially those primarily concentrated on the transarterial chemoembolization, epithelial-mesenchymal transition and cancer stem cell.…”
Section: Introductionmentioning
confidence: 99%
“…The root of Angelica sinensis (Oliv.) Diels (A. sinensis), belonging to Umbelliferae family, is identified as a multispecies of about 100 and A. sinensis is largely cultivated in the temperate regions, particularly in Africa, Asia, parts of South America [1,2]. The A. sinensis has been cultivated for 2000 years in China, mainly distributed in the northwest region (Shaanxi Province, Gansu Province) and southwest region (Yunnan Province, Sichuan Province) [3,4].…”
Section: Introductionmentioning
confidence: 99%